The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4028/www.scientific.net/amr.721.153
|View full text |Cite
|
Sign up to set email alerts
|

The Processing Characteristics and Mechanical Properties of Semi-Prepreg RTM Composites

Abstract: A novel semi-prepreg resin transfer molding (RTM) process was developed to address difficulties associated with RTM process and to improve the mechanical properties of the resulting composites. Unidirectional semi-prepregs exhibiting relatively good overlay characteristics were prepared via prepolymerization of bismaleimide resin followed by wet winding. The processing characteristics and mechanical properties of composites fabricated via semi-prepreg RTM technology were compared with those of composites produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The application of RTM in the manufacturing of longitudinally and transversely stiffened panel structures often leads to turbulent flow at the intersection of the longitudinal and transverse reinforcements, which can result in defects such as dry spots or dense voids [ 29 ]. In order to observe the microstructure of the corresponding areas in the composite stiffened panel, we selected the most challenging location, which is the integration area between the panel skin and the longitudinal reinforcement ( Figure 8 ), to investigate the internal quality of the composite stiffened panel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of RTM in the manufacturing of longitudinally and transversely stiffened panel structures often leads to turbulent flow at the intersection of the longitudinal and transverse reinforcements, which can result in defects such as dry spots or dense voids [ 29 ]. In order to observe the microstructure of the corresponding areas in the composite stiffened panel, we selected the most challenging location, which is the integration area between the panel skin and the longitudinal reinforcement ( Figure 8 ), to investigate the internal quality of the composite stiffened panel.…”
Section: Resultsmentioning
confidence: 99%
“…In order to observe the microstructure of the corresponding areas in the composite stiffened panel, we selected the most challenging location, which is the integration area between the panel skin and the longitudinal reinforcement (Figure 8 From Figure 9, it can be observed that the internal quality in the selected typical area is good, and no void defects are detected. The application of RTM in the manufacturing of longitudinally and transversely stiffened panel structures often leads to turbulent flow at the intersection of the longitudinal and transverse reinforcements, which can result in defects such as dry spots or dense voids [29]. In order to observe the microstructure of the corresponding areas in the composite stiffened panel, we selected the most challenging location, which is the integration area between the panel skin and the longitudinal reinforcement (Figure 8 From Figure 9, it can be observed that the internal quality in the selected typical area is good, and no void defects are detected.…”
Section: Composite Longitudinally and Transversely Stiffened Panel Ba...mentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental idea of this process involves using prepreg layup to fabricate features such as bosses and stiffeners within the structure, overlaying large-area dry fabric skins on the prepreg skeleton, and then co-curing them through RTM process. Compared to conventional autoclave process, this process can achieve net-size preparation of irregular contoured structures and integral stiffened panels without secondary bonding or mechanical connection methods, and compared to pure RTM process, this process does not require complex overall dry preform preparation and can improve defects such as local resin-rich areas and high porosity easily occurring in RTM process [23][24][25][26]. However, when using the prepreg-RTM co-curing process to prepare T-joint, to ensure the quality of the interface between the skeleton and skin, the compatibility between the resin systems of the prepreg laminate and RTM is essential.…”
Section: Introductionmentioning
confidence: 99%
“…However, when using the prepreg-RTM co-curing process to prepare T-joint, to ensure the quality of the interface between the skeleton and skin, the compatibility between the resin systems of the prepreg laminate and RTM is essential. If the thermophysical properties and rheological characteristics of the two resin systems are not matched, defects such as fiber wrinkling, delamination, and dense porosity are prone to occur at the interface [24,[27][28][29]. Therefore, to produce the novel T-joint with high-quality interface using the prepreg-RTM co-curing process, it is necessary to address the compatibility of the co-curing resin system and the process adaptation issues.…”
Section: Introductionmentioning
confidence: 99%